Implementasi Model Project based learning Sebagai Upaya Mengembangkan Multiple Intelligences Siswa - Muhammad Romli; Ficky Dewi Ixfina (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research is motivated by the statement that every human being has multiple intelligences called multiple intelligences, meaning that every human being has their own superior intelligence. This intelligence should be developed in schools. Unfortunately, not all teachers know the right method to develop this intelligence. Therefore, the purpose of this study is to find out what aspects of multiple intelligences develop during the implementation of project based learning at MI Al Fithrah Surabaya and the implications of implementing project based learning. The implementation of Project based learning learning is only limited to gadget addiction material which is carried out in class 3C MI Al Fithrah Surabaya. The research approach used is descriptive qualitative with the case study method. The instruments used were observation, interviews and documentation. The results showed that during the implementation of project based learning learning all aspects of students' multiple intelligences developed, namely logical mathematical intelligence, linguistic intelligence, kinesthetic intelligence, musical intelligence, interpersonal intelligence, intrapersonal intelligence, naturalist intelligence, visual spatial, except for existential intelligence which was not develop. Mathematical logical intelligence and linguistic intelligence can develop very well. In addition, the impact of the implementation of the project based learning learning model is that there are five products produced by students, namely: Madasi Medicine (Siri Leaf Eyes), Gadget Addiction Danger Videos, Puppet Games, Wormat (Tomato Carrots), Gadget Diet Benefit Posters, as well as increased academic and non-academic achievements of students.